Genome Dynamics of Adaptation and Introgression in Neotropical Palms - Pantoja, Pauline O.; Vieira, Lucas D.; Lima, Natácia E.; Sobral‐Souza, Thadeu; Bacon, Christine D.; Collevatti, Rosane G. (Journal of biogeography, 2025)
ABSTRACT Aim The combined influences of demographic dynamics and gene flow on local adaptation in plants is still poorly understood. Here, we used a genome scan approach on three closely related Neotropical palms, Acrocomia aculeata, A. intumescens and A. totai, to identify the evolutionary processes generating shared and lineage‐specific patterns of differentiation and selection across the genomic landscape. Location Amazonia, Atlantic Forest, Cerrado and Caatinga ecoregions of Brazil. Taxa Arecaceae. Methods We used target sequence capture and analysis of climatic correlation, detection of selective sweeps, balancing selection, and spatial and non‐spatial models to identify signatures of natural selection and admixture. We also determined temporal dynamics in spatial distribution and demographic changes. Results We found a higher number of lineage‐specific than shared adaptive sites (SNPs) and no evidence of selective sweeps in shared genes, suggesting lineage specific natural selection across species. Further, evidence of balancing selection in several genes was also identified in the three species. Niche‐based and coalescent models suggest that shifts in spatial range during the Quaternary caused overlapping distributions between species, leading to hybridisation between parapatric localities. Main Conclusions Interspecific hybridisation may have spread both neutral and adaptive SNPs, which may explain the shared adaptive genes between species. Taken together, we show how genomic adaptation can occur despite introgression, through evolutionary processes that likely drive similar patterns of adaptation in other organisms.